A revision of the Rhoptrobothriidae (Cestoda: “Tetraphyllidea”) - Jensen, Kirsten; Pen, Isabel A. M.; Caira, Janine N. (Zootaxa, 2021)
The Rhoptrobothriidae are one of the more enigmatic families of cestodes of elasmobranchs. Opinions on the taxonomic status of the family’s three original genera (i.e., Myzophyllobothrium, Rhoptrobothrium, and Myzocephalus) have varied over the 115 years since they were erected. Some authors have considered all three valid, others have considered Rhoptrobothrium to be a synonym of Myzopyllobothrium or a genus inquirendum, yet others have considered Myzocephalus to be a synonym of the phyllobothriid genus Thysanocephalum. All three genera were established for specimens collected from eagle rays off Sri Lanka. The erection of Mixophyllobothrium for two specimens from a cowtail stingray off India three decades ago added additional confusion to the situation, with some authors considering it valid and others a synonym of Myzocephalus. These disagreements stem largely from differences in interpretation of the complex morphology of the scolex of members of these genera. Furthermore, with the exception of Rhoptrobothrium comprising four species, each genus is monotypic. All but Rhoptrobothrium has not been considered in detail for nearly a century, largely because of a lack of available material. The taxonomic status of these genera is assessed here based on light and scanning electron microscopy, and molecular data generated from new material collected from eagle rays off Indonesian and Malaysian Borneo, Japan, Sri Lanka, and Viet Nam. Morphological work indicates that the genera differ largely only in the degree of folding of the four remi that extend from the cephalic peduncle. A molecular phylogeny based on sequence data for the D1–D3 region of the 28S rRNA gene, which include new data for eight specimens of four species, indicates that Myzophyllobothrium, Myzocephalus, and Rhoptrobothrium are not mutually monophyletic. The latter two genera and Mixophyllobothrium are considered synonyms of Myzophyllobothrium and five species are transferred to that genus. Myzophyllobothrium okamuri n. comb. is considered a species inquirendum. Myzophyllobothrium nagasawai n. sp. is described from Aetobatus narutobiei off Japan. Myzophyllobothrium narinari n. comb. is re-described based on newly collected cestodes from the type host and locality (i.e., Aetobatus ocellatus off Sri Lanka). Despite consisting of only a single genus, the family status of the group is retained in recognition of the unusual configuration of the scolex, which bears four biloculate bothridia and four remi extending from the cephalic peduncle. The ordinal placement of the family remains uncertain, but affinities with the Phyllobothriidea, rather than “Tetraphyllidea” are considered.